2014
DOI: 10.1037/a0034904
|View full text |Cite
|
Sign up to set email alerts
|

Identifying depression severity risk factors in persons with traumatic spinal cord injury.

Abstract: Likely SUD as measured by the SAVR-S was most predictive of depression symptom severity in this sample of persons with traumatic SCI. Drug and alcohol screening are important for identifying individuals at risk for depression, but screening for both may be optimal. Further research is needed on risk and protective factors for depression, including psychosocial characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…20 During this period, percentages of ASIA A, B, C, and D injuries were 39.4%, 8.7%, 21.1%, and 30.8%, respectively, and ASIA A and D injuries comprised the majority of TSCI cases. Increased attention should be paid to ASIA A patients when they encounter TSCI, as they are more prone to suffer from depressive disorders 21 and suicide. 22 Several limitations need to be considered in the current study: (1) there was a lack of information on the training and qualifications of the individuals identifying patients with TSCI in Chongqing, even in China.…”
Section: Discussionmentioning
confidence: 99%
“…20 During this period, percentages of ASIA A, B, C, and D injuries were 39.4%, 8.7%, 21.1%, and 30.8%, respectively, and ASIA A and D injuries comprised the majority of TSCI cases. Increased attention should be paid to ASIA A patients when they encounter TSCI, as they are more prone to suffer from depressive disorders 21 and suicide. 22 Several limitations need to be considered in the current study: (1) there was a lack of information on the training and qualifications of the individuals identifying patients with TSCI in Chongqing, even in China.…”
Section: Discussionmentioning
confidence: 99%
“…While injuries resulting from MVCs and falls from a large height mostly lead to complete SCIs, mainly of grade A, falls from a small height primarily cause grade D SCIs (incomplete SCI). Williams et al [22] and Thietje et al [23] reported that patients with grade A SCIs are more likely to experience depressive disorders and suicide; therefore, the families and doctors of these patients should provide more care to these patients to help prevent suicide caused by depression.…”
Section: Discussionmentioning
confidence: 99%
“…People with a mean of 3.86 ± 3.9 years of injury in outpatient rehabilitation Williams et al (33) 2014 USA given and organized on a scale from zero to three points and the result is obtained by the sum of the answers to the items that make up each of the three subscales (34) . "The depression subscale assesses symptoms like inertia; anhedonia; dysphoria; lack of interest/involvement; self-depreciation; devaluation of life and discouragement" (36) .…”
Section: Beck Depression Inventorymentioning
confidence: 99%